Does the coach leadership behavior mediates the influence of factors affecting coach leadership behavioral styles on team success - Perera, H. P. N. (International Journal of Human Movement and Sports Sciences, 2019)
The intension of this study is to conclude whether coach leadership behavior serves as a mediator amongst factors affecting said leader behavior and team success in sports. The sample for this was obtained from one hundred and sixty (n=160) athletes who participated in inter university games with special reference to Western Province Sri Lankan. Only team sports are considered and players from individual events are not considered under the current study. Coach leadership behavior was assessed through Revised Leadership Scale for Sports questionnaire (RLSS) and adopted questionnaires were utilized to measure the factors affecting it and the team success. General Linear model and Multiple Linear Regression were the methods used to analyze data. Validity and reliability of the questionnaires were measured through Correlation matrixes and Cronbach's alpha respectively. The results from the study confirm that coach leadership behavior acts as a mediator of the relationship between and factors affecting coach leadership style and team success signifying that factors affecting coach leader behavior may enhance coach behavior in the task of successful performance. Mediating effect was first tested through calculating path coefficients and further conducted the Sobel's test to validate the previous results.